PENINGKATAN PELUANG PARIWISATA UNTUK HUNIAN HOTEL DI ERA DIGITAL MELALUI PELATIHAN PEMASARAN DIGITAL DI SMK HARAPAN BERSAMA - Lourensius Hendra Putra; Prasetya Putra Nugraha; Abdul rohman marbun (Jurnal Padamu Negeri, 2025)
This Community Service Program aimed to enhance the understanding and skills of students from SMK Harapan Bersama, particularly those in the Hospitality Study Program, in applying digital marketing strategies to support increased hotel occupancy in the digital era. The training was conducted through a participatory and practical approach, covering key topics such as digital marketing fundamentals, the use of social media, Google Business Profile and OTA platforms, basic SEO techniques, and electronic word of mouth (e-WOM) strategies. Evaluation was carried out using pre-test and post-test instruments involving 35 participants, showing significant improvements across all assessed aspects. The highest increases were observed in hotel promotional content development (from 60% to 88%) and the use of social media for promotional purposes (from 55% to 85%). These results demonstrate the effectiveness of the training in strengthening students’ competencies in both practical and contextual ways. The program was perceived as highly beneficial and relevant to the needs of the hospitality industry and is recommended for continuous implementation to support vocational students’ readiness in facing digital industry demands.